Token Money or Cryptocurrency: technological Content and Economic Essence - A. V. Varnavskiy (Финансы: теория и практика, 2018)
The obligatory features of the unit of account are formulated. Distinctive characteristic properties of a set of cryptocalculation units, in particular, subsets of x-type (coin) and y-type (token) calculation units, are revealed. It is proved that these sets do not intersect. It is proposed to allocate a subset of C 2 in the set of coins, which has an additional characteristic property — functioning on the basis of a smart contract. The thesis that any settlement unit carries the cost of a resource is proved. Even for units of account with the so-called “intrinsic value” (bitcoin), the presence of a resource in its functions was found. Four characteristic properties inherent in the set of “money” (M = {money}) are disclosed and a subset DM = {digital money} is allocated, containing a set of digital Fiat money secured by the state (sets F = {fat}) and a subset P = {private}, which is actually an addition to the set F). It is proved that cryptocurrencies have characteristic properties of the set M = {money} only within their own community. The paradox of the algorithmic guarantor, reﬂecting the absence of the need for formalization of algorithmic informal institutions, is formulated. Disclosed defnitions of such concepts as “cryptocurrency”, “token economy” and “tokenization economy”. Euler circles are used to visualize the relationship between different sets of calculation units. A coherent classifcation of calculation units based on the characteristic properties of the identifed sets is formed. The results of the study can be used to form the basis of legal regulation of the circulation of digital units of account.